An fMRI examination of the neural basis of suicide attempts: The role of mentalizing in the context of mood. (6th October 2022) - Malhi, Gin S.; Das, Pritha; Outhred, Tim; Bryant, Richard A.; Calhoun, Vince D.
Abstract: Objectives: Facial emotion recognition (FER) deficits in depressed mood disorder patients contribute to suicidality. Prior research shows that intrinsic brain activity patterns are altered by attempting suicide. Therefore, we investigated in depressed patients whether differences in FER contribute to their clinical symptoms of suicide. Methods: Neural activity in response to an FER task was compared across three groups: healthy controls (HCs, N = 66), suicide non‐attempter (SNA, N = 50), suicide attempter (SA, N = 25). Modulation of brain networks by the task and functional connectivity (FC) within (using spatial map, spectral power) and between (using functional network connectivity; FNC) were examined. The contribution of these differences to suicidal symptoms in each group was also examined. Results: Patient groups displayed impaired FC both within and between networks but differed in nature and networks involved. They also showed differential modulation of networks by task, such that compared with both HC and SNA, SA displayed impaired FC within the default‐mode network (DMN) and also its task modulation. In the SA group, FC within the DMN and FNC between two lateral prefrontal networks, and its interaction with the basal ganglia network contributed significantly to the clinical symptoms of suicide. Conclusions: This study affirms differences between SA and SNA brain activity patterns and suggests that suicidal activity probably emanates via different mechanisms in these patient groups. Perhaps, over‐attribution of emotion impairs one's self‐referential thought processes and coupled with diminished emotional control this makes depressed individuals vulnerable to suicide.